Bank Cards and Ways to Improve Their Services - Nozimov Eldor Anvarovich (Research Parks Publishing LLC, 2022)
This article describes bank cards, their essence, types, services, payment systems created by banks and the experience of foreign countries in this area. It also explains the overdraft service, the content and benefits of credit cards, and suggests areas for their further development.